Technetium-99m hexamethyl propylene amine oxime granulocyte scintigraphy in Crohn's disease: diagnostic and clinical relevance. Issue 10 (October 1993) - Sciarretta, G; Furno, A; Mazzoni, M; Basile, C; Malaguti, P
Abstract : Scintigraphy with autologous granulocytes labelled by technetium-99m hexamethyl, propylene amine oxime (99mTc-HMPAO) was performed in 103 Crohn's disease patients and 52 healthy controls. In 31 patients endoscopic and histologic activity was compared with scan activity index. In the 98 patients with a positive scan, the extent of Crohn's disease, assessed by scintigraphy, was compared with that evaluated by small bowel x ray or colonoscopy with biopsies. In 48 patients, Crohn's disease activity index, activity index, simple index, erythrocyte sedimentation rate, C-reactive protein were correlated with the scan results. In 16 patients the five parameters and scan were repeated after treatment with methyl-prednisolone (10 cases), enteral nutrition (3), and 5-acetylsalicylic acid (3). The results showed that 99mTc-HMPAO granulocyte scan had a 95% sensitivity and 100% specificity to detect active inflammation; it correctly showed an abscess or a fistula in all the 24 cases found. The correlation between histological inflammatory activity and scan activity index was highly significant (r = 0.85; p < 0.01), less significant (r = 0.65; p < 0.01) between endoscopy and scan activity index. The evaluation for the extent of Crohn's disease by scan was completely correct in the small bowel (100%) and 93% correct in the large bowel. No correlation was seen between the three clinical activity parameters and scanning; in more than 80% of the cases in remission on the basis of a clinical or laboratory index, scintigraphy remained positive. Medical treatment was effective on the clinical indices but not on the active inflammation in the ileum, whereas it led to a negative scan in 5/11 cases in the large intestine. Scintigraphy with 99mTc-HMPAO granulocyte plays an important part in Crohn's disease for the diagnosis of complications, for activity and assessment of the extent, and for the treatment results evaluation.